A MULTIPRONGED APPROACH TO ACHIEVE SIGNIFICANT LDL CHOLESTEROL REDUCTION: A CASE FROM A METABOLIC CLINIC - Susinadan, Jolyn Rumefla; Ng, Ooi Chuan; Arif, Nurafiza Mohd (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Lowering low-density lipoprotein cholesterol (LDL-C) is crucial in reducing cardiovascular disease (CVD) risk, especially in patients with metabolic syndrome and obesity. While statins remain the primary pharmacological inter- vention, a comprehensive approach incorporating lifestyle changes and adjunctive therapies can yield remarkable results. This case highlights the successful application of a multipronged strategy in a metabolic obesity clinic. CASE A 38-year-old Malay female with obesity, type 2 diabetes mellitus (T2DM), dyslipidemia, and fatty liver was followed up for lipid management. Upon her initial visit to the metabolic obesity clinic two years ago, her LDL-C was markedly elevated at 5.7 mmol/L. She was started on atorvastatin 20 mg nightly alongside lifestyle modifications. To further improve metabolic control, Contrave (naltrexone-bupropion) was introduced initially for weight management but was sequentially switched to Rybelsus (oral semaglutide) over the past year. A structured dietary approach, including a low-calorie diet with reduced refined carbohydrates and increased fiber intake, was implemented along with gradual exercise initiation. Over two years, her LDL-C dropped dramatically from 5.7 mmol/L to 1.6 mmol/L. Concurrently, triglycerides improved, HDL-C increased, and her HbA1c decreased from 7.2% to 5.6%. She also achieved clinically significant weight loss, from 91 kg to 86 kg. This comprehensive inter- vention led to substantial cardiometabolic benefits. CONCLUSION This case demonstrates that a multipronged approach integrating statins, novel glucose-lowering agents and life- style modifications can achieve exceptional LDL-C reduction and broader metabolic improvements. Clinicians should consider a patient-centered, holistic strategy to optimize lipid control and long-term cardiovascular outcomes.